(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
This study aims to analyze the sales promotion strategies implemented by BMA (Baju Murah Anak) on the Shopee marketplace, one of the largest e-commerce platforms in Indonesia. Although BMA has undertaken various promotional efforts, its sales still show a fluctuating trend and has not fully achieved its targets. Therefore, this study uses a descriptive qualitative approach with data collection techniques through direct observation, interviews with owners and consumers, and documentation of promotional activities. The research focused on four main strategies: sampling, price packages, refunds, and premiums. The results indicate that the strategy of providing samples to affiliates is effective in increasing brand visibility and exposure among new consumers, although its contribution to increasing direct sales is still limited. The price package and premium strategies have proven more effective in encouraging large purchases and strengthening customer loyalty. On the other hand, the refund strategy is considered important for building a sense of security and consumer trust, although it still faces obstacles related to the speed and efficiency of service. Overall, the implementation of these four strategies has had a positive impact on BMA’s brand image and credibility. However, their effectiveness needs to be continuously evaluated and adjusted to the dynamics of the highly competitive digital market. The practical implications of this research can serve as a reference for MSMEs in designing more adaptive, innovative, and consumer-oriented promotional strategies on marketplace platforms such as Shopee.